PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN MOBILE LEARNING BERBASIS HTML 5 UNTUK GURU-GURU IPA SE-KECAMATAN PAMEUNGPEUK - Asep Rohayat; Hudiana Hernawan; Leni Sri Mulyani; De Budi Irwan Taufik; Diah Ika Putri; Siti Nurkamilah (Jurnal Pekemas, 2018)
Educational media is one of the factors that influence the learning process. One form of educational media that is effectively and efficiently used in the learning process is mobile learning. Because, by using mobile learning learning can be done anywhere and anytime, apart from that learning by placing the smart phone on will motivate students who in the digital era like today who prefer to operate smart phones. However, the skills and expertise possessed by teachers as educators and instructors as well as media makers and materials are still minimal. Therefore, the Biology education of IPI Garut held a training on Making Mobile Learning Media Based on Html 5 for Ipa Teachers in the Districts of Pameungpeuk to make teachers trained in making good mobile-based learning media. This training was held in Pamengpeuk District, which was located at MAN 3 Pamengpeuk, Garut Regency. The activity was held on December 22, 2018. This activity was attended by 17 teachers who were members of the Biology MGMP. The data obtained is data from the training participants in the form of questions raised about the activities carried out. The data analysis technique used is quantitative descriptive. The results obtained by the training on the use of mobile lerning are very helpful for teachers in making learning media. effectiveness in the use of learning media based on mobile learning is considered good by most teachers, but there are also some teachers who judge it to be less effective due to certain factors, such as schools implementing regulations that students are prohibited from bringing gadgets to school. However, basically the use of educational media by using mobile learning can have a major impact on creativity and effectiveness during the learning process.